Bantuan Luar Negeri sebagai Intrumen Diplomasi: Studi Kasus Bantuan Kemanusiaan Rusia kepada Donbas dalam Konflik Rusia-Ukraina 2014-2015 - Buntaran, Veronika Suci Novitasari; Rosyidin, Mohamad (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
The Russian-Ukrainian conflict reached its peak in 2014. Conflict exacerbated by theexistence of war crimes has caused a humanitarian crisis with various socio-economicimpacts and also increased the number of refugees. Since August 2014, Russia has decidedto issue humanitarian aid policy in the conflict. This research analyzes the motives ofRussia's humanitarian aid policy in Donbas using the theory of neoclassical realism. Theresults reveal that the policy is a strategy to increase Russian influence in Ukraine.Anarchic international structure with nations competing for power became an independentvariable in this research. Putin's view on seeing Russia as a major power and Russia's rolein the international world becomes an intervening variable that translates the internationalsituation into the policy. The strategy of humanitarian aid policy with the motive ofmaintaining influence in Ukraine will also have an impact on the increasing position ofRussia in regional countries that can strengthen its status as a global player.